2010
DOI: 10.1021/ac902975r
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Photothermal Absorbance Detector for Use with Microfluidic Devices

Abstract: The development of a photothermal absorbance detector for use with microfluidic devices is described. Unlike thermooptical techniques that rely on measuring refractive index changes, the solution viscosity is probed by continuously monitoring solution conductivity. Platinum electrodes microfabricated on a quartz substrate and bonded to a substrate containing the microchannels enable contact conductivity measurements. The effects of excitation frequency and voltage, electrode spacing, laser power, and laser mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…showed that microfluidic-based photothermal absorbance detection could be achieved using contact conductivity measurement with platinum electrodes and a high frequency AC excitation signal. [32] A marked increase in the overall sensitivity and agreement with theoretical calculations was shown, however, a limitation to the applied excitation signal due to electrode degradation was observed. While a limit of detection (SNR = 3) of 5 nM for DABSYL-tagged glucosamine was achieved, any misalignment between the detection region and the laser beam could cause a loss in signal intensity and possibly damage the electrodes.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…showed that microfluidic-based photothermal absorbance detection could be achieved using contact conductivity measurement with platinum electrodes and a high frequency AC excitation signal. [32] A marked increase in the overall sensitivity and agreement with theoretical calculations was shown, however, a limitation to the applied excitation signal due to electrode degradation was observed. While a limit of detection (SNR = 3) of 5 nM for DABSYL-tagged glucosamine was achieved, any misalignment between the detection region and the laser beam could cause a loss in signal intensity and possibly damage the electrodes.…”
Section: Introductionsupporting
confidence: 65%
“…While the maximum signal intensity continued to increase with excitation voltage, a signal of 5 V p–p was chosen to allow comparison to previously published results using a metal electrode based microchip. [32] With the metal electrode microchip, the photothermal SNR increased with excitation frequency up to the lock-in amplifier’s limit (102 kHz), however this was not seen with the PGE microchip (Figure 2b). Although the photothermal signal intensity increased linearly with the excitation frequency, the baseline noise also increased possibly because the background signal nulling through the PGEs has a frequency limit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The property of light absorption by molecules is one of the most used and easy to implement. It can be used to create photothermal lenses whose refractive index varies with the analytes concentration [2,3]. As molecules present numerous absorption bands in the visible spectral range, there is a need for a shift of the working wavelengths from the usual near Infra-red [1.3À 13À 1.5] μm telecom band towards the [0.4À 04À 0.8] μm visible one.…”
Section: Introductionmentioning
confidence: 99%